Constructing International Policy Research: the role of CERI/OECD - Schuller, Tom (European Educational Research Journal, 2005)
This article discusses how the Organisation for Economic Cooperation and Development’s Centre for Educational Research and Innovation (CERI) addresses the task of conducting international policy research. The article begins with a descriptive account of CERI’s work, including the way member countries shape the research agenda. Several issues which relate to how research evidence is compiled within an international context are addressed. First, why the supposed priority area of lifelong learning is only weakly supported by systematic research is considered. The author raises the question of how we are to judge the quality and impact of international research work, especially where it is policy-related. He suggests that an increasing focus on the outcomes ofeducation raises questions about causality in a policy research context. This leads to some brief consideration of evaluation of research, and of the country as a unit of methodological analysis. Finally, he asks what might be meant by learning from international experience.
Keywords: méthodes de recherche; politique éducative; utilisation des recherches